2015
DOI: 10.1080/10807039.2015.1100515
|View full text |Cite
|
Sign up to set email alerts
|

Risk and benefit judgment of excreta as fertilizer in agriculture: An exploratory investigation in Rwanda and Uganda

Abstract: This research explores the use of psychometric techniques to improve understanding of psychological mechanisms underlying judgment of excreta as fertilizer in agriculture including other excreta-related activities. Participants consisted of environmental health students, smallholder farmers, and traders in rural and urban Rwanda and Uganda. The finding reveals an inverse relationship between risk and benefit judgments. This relationship holds for the three groups of participants with significant risk and benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…The study finds that socioeconomic characteristics and personal needs, as well as environmental factors such as soil properties, irrigation water, access to agricultural inputs, market demands, weather conditions, and extension activities all influenced the adoption of sustainable agricultural practices (Bopp et al, 2019). Recently, factors such as farmers’ perception of how easy the practice is to apply (Wehmeyer et al, 2020), benefit perceptions (Connor et al, 2020; Ekane et al, 2016), and perceptions of farmer satisfaction and expectations from the introduction process (Wehmeyer et al, 2020) have also been shown to affect the level of adoption of new agricultural technologies and practices.…”
Section: Introductionmentioning
confidence: 99%
“…The study finds that socioeconomic characteristics and personal needs, as well as environmental factors such as soil properties, irrigation water, access to agricultural inputs, market demands, weather conditions, and extension activities all influenced the adoption of sustainable agricultural practices (Bopp et al, 2019). Recently, factors such as farmers’ perception of how easy the practice is to apply (Wehmeyer et al, 2020), benefit perceptions (Connor et al, 2020; Ekane et al, 2016), and perceptions of farmer satisfaction and expectations from the introduction process (Wehmeyer et al, 2020) have also been shown to affect the level of adoption of new agricultural technologies and practices.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the productive use of sewage sludge in agriculture, topsoil production, and covering landfills with sewage sludge are generally acceptable practices despite the potential risks these practices may have on the environment (SOU, 2020:3). Even the application of other resources such as cattle manure and pig slurry on agricultural land is relatively more acceptable, even though these substances have been shown to also pose risks to human and environmental health (Pell, 1997;Köpke et al, 2007;Polprasert, 2007;Zhang, 2011;Dufour et al, 2012;Ekane et al, 2016;Pedersen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Further, this shift challenges the notion that mere utility of an innovation leads to acceptance and adoption of that innovation (O'Keefe et al, 2015;Ekane, 2020). For instance, in the case of the use of excreta as fertilizer in agriculture Ekane et al (2016) show that individuals do not rely only on risk management information they receive concerning excreta and related risks but also depend, to an extent, on their feelings about these substances when making judgments and decisions regarding the purpose for using excreta as fertilizer and the level of exposure they can tolerate and manage. This is explained by the inverse relationship between risk and benefits in a person's mind (Slovic, 2000;Slovic et al, 2002Slovic et al, , 2004Ekane et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations